+Lovemarks: The Future Beyond Brands - Kevin Roberts (New York powerHouse Books, 2005)
From the worldwide CEO of Saatchi & Saatchi comes an entertaining, elucidating, and inspiring vision of the rejuvenation of brands through the power of love and the responsibility of business to fulfill one of its key functions: to make the world a better place.
Keywords: Nonfiction; Marketing; Business; Design; Art design; Forecasting; Advertising; Trademarks; Global Citizenship (BIN1064-N)